Identification and quantification of surfactin, a nonvolatile lipopeptide in Moutai liquor - Zongxiao Chen; Qun Wu; Li Wang; Shuang Chen; Lin Lin; Heyu Wang; Yan Xu (International Journal of Food Properties, 2020)
Surfactin as a nonvolatile cyclic lipopeptide has attracted great attention over the past few decades. This work focused on identification, quantification, and tracing of surfactin in Moutai liquor by ultra-performance liquid chromatography coupled with triple quadrupole tandem mass spectrometer. Our results showed that surfactin was mainly produced in Daqu making stage and stacking fermentation stage, and it increased to 1421 ± 22 μg kg–1 in the liquor fermentation stage. In addition, five strains of Bacillus spp. (MT1-MT5) were isolated from Daqu to produce surfactin, and the highest surfactin production reached to 51 ± 1 mg L–1. Therefore, Bacillus spp. played an important role in the production of surfactin. This work detected surfactin in Chinese liquor, and analyzed the concentration during the liquor fermentation. This work would facilitate the research in nonvolatile compounds of distilled liquor and shed new light on flavor–omics in Chinese liquor.